Social Capital and Economic Performance of Financial Cooperatives: Evidence from the Amhara Region - Yayeh, Fentahun Admassu; Mulugeta, Wondaferahu (Technium EconomiA, 2024)
Financial cooperatives emerged in the mid-1800s, in response to economic crises and marginalization. The response was an institution of people-centered collective action that was not driven by the state or the market. Scholars have analyzed its contribution to development worldwide, yet its position in markets, its social capital-based characteristics, and the role of social capital in financial cooperatives have been not broadly investigated in Ethiopia. Thus, this study seeks to analyze the various aspects of social capital and examines the effects of social capital on financial cooperatives’ economic performance. Social capital is indicated in terms of relational, cognitive, and structural dimensions. Analysis was made based on both the quantitative data and qualitative information a combination of primary and secondary data. Primary data was collected in a survey of randomly selected 348 members of all 27 cooperatives savings and credit unions in the Amhara region using structured questionnaires. Key informant interviews and focus group discussions were also carried out. The results revealed that higher levels of structural, relational, and cognitive social capital significantly and positively affect members’ participation in savings. Moreover, structural and relational dimensions of social capital significantly and positively influence economic performance. Whereas the deficiency of cognitive social capital; that is, a lack of understanding of shared mission and goal between members significantly disturbs the economic performance of cooperative saving and credit unions. We can safely conclude that social capital generated in members and collective actions, based on strong trust, cooperation, and common mission and goal understanding can lead cooperatives saving and credit unions to success. To grow and expand the economic performance of financial cooperatives, the cooperative’s policy must be focused and geared to the improvement of the social capital dimensions to enhance its service delivery and contribute more to the economic development of the region and the country at large.